THE SOCIOLINGUISTICS OF BUSINESS NAMES IN LAGOS, NIGERIA - Obiorah, Kenneth; Adetoro, Banwo (Armenian Folia Anglistika, 2025)
This study examines the sociolinguistic dimensions of business names in Lagos, Nigeria, analyzing the linguistic strategies employed in their formation and the socio-cultural factors influencing their selection. It also classifies business names based on their linguistic structures and sources. Data were collected from small and local businesses in Lagos, as well as registered business names from the Nigerian Corporate Affairs Commission (CAC) database. Findings reveal that business names in Lagos are created through various linguistic mechanisms, including blending, abbreviation, and coinage. Additionally, graphology, pronunciation, and multicultural considerations play a crucial role in business naming practices in Nigeria’s diverse linguistic landscape. The study highlights how business names serve as identity markers, branding tools, and cultural signifiers, influencing customer perception and marketability. A well-crafted business name enhances brand recognition, fosters consumer engagement, and ensures competitiveness in both local and international markets. Moreover, in an era of online commerce and social media marketing, business names must be linguistically adaptable and culturally resonant to appeal to diverse audiences. This study contributes to the broader field of sociolinguistics by providing insights into the intersection of language, business identity, and cultural dynamics in Lagos, offering valuable implications for entrepreneurs, linguists, and brand strategists.
Keywords: Business names; Language; Naming Practice; Sociolinguistics; Nigeria